Low-density lipoprotein cholesterol goal attainment and treatment patterns in a cohort of >143, 000 patients with atherosclerotic cardiovascular disease in Ontario, Canada. (25th November 2020) - Fairbairn, M; Oh, P; Goeree, R; Rogoza, R.M; Packalen, M; Pericleous, L; Motsepe-Ditshego, P; Colgan, S; Goodman, S.G
Abstract: Background/Introduction: Limited real-world data are available on attainment of low-density lipoprotein cholesterol (LDL-C) treatment goals in patients with atherosclerotic cardiovascular disease (ASCVD) in Canada. Purpose: A retrospective observational study was conducted to describe types of ASCVD events/procedures, time between events and use of lipid lowering treatment (LLT) in patients who did not achieve LDL-C goal. Methods: Patients in Ontario ≥65 years with a primary ASCVD event/procedure between 1 Apr 2005 and 31 Mar 2016, treated with an LLT and with index and follow up LDL-C values were identified from claims data at the Institute for Clinical Evaluative Sciences data repository. Patients were assessed over a 1-year follow up period for LDL-C goal attainment (<2.0 mmol/L or 50% reduction from index LDL-C) and analysed by LLT and by index event type. Results: Overall, 28% of 143, 302 patients ≥65 years on LLT failed to attain LDL-C goal at follow up (Figure). The proportion of patients failing to achieve LDL-C goal decreased from 35% to 22% over the 11-year study period. Mean time between index and follow up LDL-C (based on lowest score >2 weeks and up to 1 year after index LDL-C) was 203±97 days. When analysed by low-, moderate- or high-intensity statin, 57%, 30%, and 22% of patients failed to achieve LDL-C goal at follow up, respectively. Conclusions: In this study, more than 1 in 4 patients with ASCVD in Ontario failed to achieve guideline recommended LDL-C goal despite treatment. In particular, ∼1 in 3 patients with cerebral and peripheral arterial disease were not at goal. An opportunity exists to better manage these high risk ASCVD patients with further statin intensification and additional LLTs This study made use of de-identified data from the ICES Data Repository, which is managed by the Institute for Clinical Evaluative Sciences with support from its funders and partners: Canada's Strategy for Patient-Oriented Research (SPOR), the Ontario SPOR Support Unit, the Canadian Institutes of Health Research and the Government of Ontario. The opinions, results and conclusions reported are those of the authors. No endorsement by ICES or any of its funders or partners is intended or should be inferred. Parts of this material are based on data and/or information compiled and provided by CIHI. However, the analyses, conclusions, opinions and statements expressed in the material are those of the author(s), and not necessarily those of CIHI Funding Acknowledgement: Type of funding source: Private company. Main funding source(s): Amgen Canada Inc.